For a Minor Administration: The Case of the Bailinho da Tia Naná - Gontijo Martins, Paula; de Oliveira Corrêa, Marcos Paulo; de Pádua Carrieri, Alexandre (Organizações & Sociedade, 2023)
Adopting the collaborative work of Gilles Deleuze and Félix Guattari as a theoretical and methodological framework, the primary objective of this article is to argue for a minor administration. To this end, we seek to provide clues, hints, and glimpses of other forms of being and coexisting that expand, re-elaborate and tighten the conventional practices of the management universe – whether in terms of their ways of thinking and producing knowledge or their ways of organizing. Through the mapping of the immanent forces operating in the lives of women who gather to dance at the Bailinho da Tia Naná – a popular dance venue targeted at the elderly, located in downtown Belo Horizonte, Minas Gerais, Brazil – we aimed not only to reveal rigid segmentarities but also (and this is where the difference lies) to focus our attention on the appositions, inventions, that which leaks, and escapes, that which resists binary and functionalist organizations, that which escapes the colonization of our vital forces of creation and transcreation in micropolitical relations. As far as the concept of ordinary management and Organizational Studies are concerned, we sought to identify in everyday life whatever breaks with, changes, deviates from the norms, and gives birth to difference; a form of management that cares about the potency, joy, multiplicity, complexity, and interdependence inherent to the ways of organizing and composing the betweenness of ordinary, historicized, localized and real lives.